2011
DOI: 10.1095/biolreprod.110.090282
|View full text |Cite
|
Sign up to set email alerts
|

SRY Directly Regulates the Neurotrophin 3 Promoter During Male Sex Determination and Testis Development in Rats1

Abstract: Neurotrophin 3 (Ntf3) is expressed in Sertoli cells and acts as a chemo-attractant for cell migration from the mesonephros into the developing testis, a process critical to the early morphological events of testis cord formation. The male sex-determining gene Sry initiates the process of testicular development. Sox9 is a key regulator of male sex determination and is directly regulated by SRY. Information on other downstream target genes of SRY is limited. The current study demonstrates an interaction of SRY w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…The ChIP-Chip arrays identified the presence of Tcf21 in the SRY ChIP [27], Figure 1. Our previous studies have also found Ntf3 a direct downstream target of SRY in the rat [26]. Both Tcf21 and Ntf3 have distinct functions in testicular morphogenesis [28], [29], [42] and were detected in the SRY ChIP-Chip assay.…”
Section: Discussionmentioning
confidence: 78%
“…The ChIP-Chip arrays identified the presence of Tcf21 in the SRY ChIP [27], Figure 1. Our previous studies have also found Ntf3 a direct downstream target of SRY in the rat [26]. Both Tcf21 and Ntf3 have distinct functions in testicular morphogenesis [28], [29], [42] and were detected in the SRY ChIP-Chip assay.…”
Section: Discussionmentioning
confidence: 78%
“…Treatment with a TRKC receptor tyrphostin inhibitor, AG879, was found to inhibit seminiferous cord formation and mesonephros cell migration and also decreased the expression of Sox9, a downstream sex differentiation gene regulated by SRY (Cupp et al 2003). The action of NT3 as a chemoattractant for cell migration from the mesonephros into the developing gonad seems to be regulated by SRY via a physical interaction between SRY and the Ntf3 promoter that has been observed both in vitro and in vivo (Clement et al 2011).…”
Section: The Nt3-trkc Signaling Modulementioning
confidence: 83%
“…Rat tissue was chosen for technical reasons because of its suitability for the use with primary antibodies raised in mouse and rabbit. Embryonic XY and XX gonads were analyzed at the developmental stage 15.5 dpc, which corresponds to ϳ14 dpc in mice (37). A clear overlapping expression of KDR and WT1 was seen in the seminiferous cords of embryonic XY gonads (Fig.…”
Section: Wt1 Stimulates Kdr Expression In Embryonic Gonadsmentioning
confidence: 99%